Systemic cytokine profiles of CD4+ t lymphocytes correlate with clinical features and functional status in stable COPD - Uzeloto, Juliana Souza [UNESP]; de Toledo-Arruda, Alessandra Choqueta; Silva, Bruna Spolador de Alencar [UNESP]; Golim, Marjorie de Assis [UNESP]; Braz, Aline Márcia Marques [UNESP]; Grigoletto, Fabiano Francisco de Lima Isis [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (Taylor & Francis, 2020)
Aims: To evaluate the expressions of intracellular cytokines in CD4+ T lymphocytes and to investigate the correlation between biomarker expressions and clinical and functional characteristics of stable COPD patients. Patients and Methods: Peripheral blood was collected from 36 COPD patients, and the expression of cytokines (IL-8, IL-13, IL-17, IL-6, IL-2, IL-10, and TNF-α) in T lymphocytes CD4 + was investigated. In addition, lung function, dyspnea symptoms, quality of life, vital signs, body composition, level of physical activity, peripheral muscle strength, and functional capacity were assessed. Results: Individuals with greater bronchial obstruction present a higher proportion of CD4 + IL-2 + lymphocytes compared to individuals with less severe bronchial obstruction. We found a positive correlation between the expression of the cytokines IL-13, IL-17, IL-6, IL-2, IL-10, and TNF-α in CD4+ T lymphocytes. In addition, we found a positive correlation between CD4+ IL-10+ T lymphocytes and lower limb muscle strength and a negative correlation between CD4+ IL-8+ T lymphocytes and peripheral oxygen saturation and steps per day. Conclusion: Systemic CD4+IL-2+, IL-8+, and IL-10+ T lymphocytes presented a correlation with clinical characteristics and functional status in stable COPD.
Keywords: Chronic obstructive pulmonary disease; Flow cytometry; Inflammation; Phenotype